Incidence of The Bowel, Bladder, and Sexual Dysfunction Following Surgery for Colorectal Malignancy - Pokharel, Nabin; Katwal, Gaurav; Adhikari, Subodh Kumar (Journal of Nepal Health Research Council, 2019)
Background: Colorectal malignancy is a very common disease of the gastrointestinal tract. Surgery following neoadjuvant chemoradiotherapy has been found to improve the survival of the patients with colorectal carcinoma. Research on bowel, bladder and sexual dysfunction following colorectal surgery remains limited in Nepal. The aim of this study is to evaluate the incidence of the bowel, bladder, and sexual dysfunction after colorectal surgery. Methods: It is a cross-sectional study carried out at National Academy of Medical Science, Bir hospital. Patients who underwent low anterior resection and abdominoperineal resection with curative intention post neoadjuvant chemoradiotherapy were included in the study. Results: A total of 26 patients [20 (76.9%) males and 6 (23.1%) females] who underwent surgery for the colorectal malignant disease were included. 24 (92.30%) underwent low anterior resection and 2(7.6%) patient underwent abdominoperineal resection respectively after neoadjuvant chemo radiotherapy. 19(79.16%) of the patients developed bowel dysfunction with mean low anterior resections score of 22.88±4.394. And 5(20.83%) had normal bowel function. Bladder dysfunction was seen in 3 (11.5%) patients. And rest of the 23 (88.5%) patient had normal bladder function. In males, Sexual Dysfunction was observed in 11 (42.3%)and no sexual dysfunction was observed in 15(57.69%). While in females, 38.46% had no sexual desire and 50% had dyspareunia due to vaginal dryness. Conclusions: This study clearly demonstrated a higher incidence of bowel and sexual dysfunction compared to bladder dysfunction following low anterior resection and abdominoperineal resection for colorectal malignant diseases. Keywords: Bowel; bladder; sexual dysfunction; low anterior resection;abdominoperineal resection.